Direct effect of the 13-valent pneumococcal conjugate vaccine use on pneumococcal colonization among children in Brazil. Issue 36 (23rd August 2019) - Neves, Felipe P.G.; Cardoso, Nayara T.; Cardoso, Claudete A.A.; Teixeira, Lúcia M.; Riley, Lee W.
Highlights: First report in Brazil of the PCV13 direct effect on pneumococcal carriage. One quarter of the children immunized with PCV13 was colonized. Colonization with PVC13 serotype was rare. Multidrug-resistant serotype 6C and non-typeable isolates were found. Abstract: Background: The 13-valent pneumococcal conjugate vaccine (PCV13) has been commercially available in Brazil since 2010. We investigated the carriage prevalence, capsular types, and antimicrobial resistance among pneumococci isolated from children immunized with PCV13 in Brazil. Methods: We analyzed 500 children < 6 years old attending public (n = 270) and private (n = 230) clinics in Niterói/RJ, Brazil, in 2014. We determined the antimicrobial susceptibility and capsular types for all isolates. Results: Thirty-eight (7.6%) of 500 children had received at least one PCV13 dose. Since only two (0.7%) of 270 children at the public clinic were vaccinated with PCV13, major analyses focused on 36 (15.7%) of 230 children attending private clinics. Nine (25%) of 36 children were pneumococcal carriers. Characteristics associated with carriage were age ≥ 2 years, cough/expectoration, and childcare center attendance (p ≤ 0.01). The capsular types found were 15B/C (n = 2), 6C, 11A/D, 16F, 23A, and 23F. Two isolates were non-typeable (NT). Three (33.3%) isolates were multidrug resistant. We found four (44.4%) penicillin non-susceptible pneumococci, with penicillin and ceftriaxone MICs ranging from 0.12 to 4.0 µg/ml and 0.023–0.5 µg/ml, respectively. We also detected two (22.2%) erythromycin-resistant isolates (MICs of 3.0 and 256 µg/ml). Conclusions: Colonization with PCV13 serotype was rare among the vaccinated children. Increasing PCV13 coverage might help reduce the frequency of major serotypes currently associated with invasive pneumococcal diseases in Brazil, such as 3 and 19A. The isolation of multidrug-resistant serotype 6C and NT isolates in carriage, however, requires close monitoring.